2014
DOI: 10.1055/s-0033-1340867
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethylated Internal Alkynes: Versatile Building Blocks for the ­Preparation of Various Fluorine-Containing Molecules

Abstract: Trifluoromethylated alkynes (CF 3 alkynes) are among the most powerful synthetic intermediates for the preparation of fluorine-containing materials. In this account, our recent advances on the synthesis and reactions of trifluoromethylated alkynes are described. 1 Introduction 2 Synthesis of Trifluoromethylated Alkynes 3 Addition Reactions of H-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…[3] Taking into account the importance of trifluoromethyl group, a tremendous effort has been paid towards the development of synthetic methodology for the introduction of trifluoromethyl group into diverse organic frameworks. [4][5][6][7][8][9][10][11][12][13][14] Due to the advancement of synthetic organic chemistry, the CF 3 substituted molecules can be accessed through two major routes: (i) Direct trifluoromethylation reaction using various reagents, [4] and (ii) using the prefunctionalized CF 3 group containing building blocks. [5] For the first route there have been various reviews that deal with different types of trifluoromethyl reagents based on their electronic nature such as radical, [6] electrophilic, [7] or nucleophilic [8] or the types of strategy used for the construction of trifluoromethylated molecules using these reagents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Taking into account the importance of trifluoromethyl group, a tremendous effort has been paid towards the development of synthetic methodology for the introduction of trifluoromethyl group into diverse organic frameworks. [4][5][6][7][8][9][10][11][12][13][14] Due to the advancement of synthetic organic chemistry, the CF 3 substituted molecules can be accessed through two major routes: (i) Direct trifluoromethylation reaction using various reagents, [4] and (ii) using the prefunctionalized CF 3 group containing building blocks. [5] For the first route there have been various reviews that deal with different types of trifluoromethyl reagents based on their electronic nature such as radical, [6] electrophilic, [7] or nucleophilic [8] or the types of strategy used for the construction of trifluoromethylated molecules using these reagents.…”
Section: Introductionmentioning
confidence: 99%
“…[4,[6][7][8] The reviews on second route have also been reported with individual fluorinated building blocks. [9] For trifluoromethyl group, only few building blocks have been explored, for example aryl trifluoromethyl ketones, [10] trifluoroacetoacetate, [11] trifluoromethylated internal alkynes, [12] α,β-unsaturated trifluoromethylketones, [13] etc. To this end, Billard has reported a short review on β-trifluoromethyl-α,β-unsaturated carbonyl compound, mainly the ester counterpart in 2006, [14a] however an important building block remained unaddressed, i.e β-trifluoromethyl-α,β-unsaturated ketones, which has tremendously gained attention in the recent years to the organic chemists due to its availability and versatility of reactions it undergoes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, numerous fluorine-containing organic materials have been developed because chemical reactivity and material properties are dramatically influenced by the unique characteristics of fluorine, e.g., the largest electronegativity of all elements, the second smallest atom has extensively studied efficient synthetic protocols for organofluorine molecules containing CF3 groups [14,15] and CF2CF2 fragments [16,17]. More recently, we have also developed a significant interest in functional materials, e.g., liquid-crystalline (LC) and photoluminescence (PL) materials, based on fluorinated π-conjugated molecules such as pentafluorophenyl-containing tolane [18] and bistolane molecules [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the fascinating molecular properties of organofluorine compounds exerted by the fluorine atom, our research group has devoted sustained effort to the development of novel biologically active fluorinated substances and high-functional fluorinated materials thus far [ 7 9 ]. Our recent interest inspired by the discovery of fluorinated liquid-crystalline (LC) molecules [ 10 11 ] led to the rational molecular design and synthesis of a family of novel fluorinated LC molecules that possess large negative dielectric anisotropy (Δε).…”
Section: Introductionmentioning
confidence: 99%